Strategies for Preserving Cultural Tourism in Bulungan Regency, North Kalimantan Province - Evelyn Imanuella Dhika Putri Patulak; Anggraeny Puspaningtyas; Eddy Wahyudi (Journal of Political and Governance Studies, 2026)
Background This research focuses on examining strategis to preserve and develop cultural tourism in Bulungan Regency, North Kalimantan. The study places cultural heritage as an important element that strengthens regional identity and supports sustainable tourism. Through this research, the author identifies strategic issues, reviews internal and external conditions, and explains how stakeholders participate in cultural tourism development at the local level. Methods The researcher conducted the study using a qualitative method by gathering data through interviews, observations, and documentation. The analysis follows the stages of strategic planning, which include identifying strategic issues, analyzing internal and external environments using the SWOT approach, and assessing the roles of relevant stakeholders. These analytical steps serve as the basis for formulating strategies that support cultural preservation and tourism development. Results The findings show that cultural tourism in Bulungan Regency has strong cultural values and active community involvement, but still faces limitations such as weak infrastructure and low institutional support. The study also identifies opportunities from the growing interest in cultural tourism and government support, along with threats from modernization Stakeholder analysis indicates that government agencies, cultural communities, and tourism actors hold important roes in carrying out cultural preservation efforts. Conclusions This study provides strategic directions to reinforce cultural tourism development by emphasizing collaboration, institutional strengthening, and sustainable cultural management.